2017
DOI: 10.1177/1357633x17696587
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of satisfaction with teledermatology

Abstract: Background The two most commonly used modalities of teledermatology (TD) are store-and-forward (SF) and live-interactive (LI) TD. Existing studies have not compared these tools with respect to patient and provider satisfaction. Objective To systematically review all published studies of patient and provider satisfaction with SF and LI TD. Methods PubMed, EMBASE, and Cochrane databases were systematically searched for studies on provider or patient satisfaction with SF or LI TD between January 2000 and June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 56 publications
5
81
0
2
Order By: Relevance
“…The shortage of recent studies on patients’ and providers’ satisfaction is additionally emphasized by a review from 2018, which investigated satisfaction with LI and S&F teledermatology applications. This review indicated patients’ and providers’ overall satisfaction with LI and S&F teledermatology but, thereby, did not find many recently published studies . Nowadays, we would expect higher feasibility scores as technology has improved and people are more accustomed to digital progress.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The shortage of recent studies on patients’ and providers’ satisfaction is additionally emphasized by a review from 2018, which investigated satisfaction with LI and S&F teledermatology applications. This review indicated patients’ and providers’ overall satisfaction with LI and S&F teledermatology but, thereby, did not find many recently published studies . Nowadays, we would expect higher feasibility scores as technology has improved and people are more accustomed to digital progress.…”
Section: Discussionmentioning
confidence: 89%
“…This review indicated patients' and providers' overall satisfaction with LI and S&F teledermatology but, thereby, did not find many recently published studies. 44 Nowadays, we would expect higher feasibility scores as technology has improved and people are more accustomed to digital progress. More current studies on feasibility are therefore important.…”
Section: Discussionmentioning
confidence: 99%
“…For both procedures, a limitation was the loss of the face-to-face patientphysician relationship, which may be critical since a melanoma is diagnosed early, at a severe stage, or in the ageing population [35,40,49,73]. Positive perspectives may improve compliance to referrals and possibilities for the patient to participate actively in his/her health [24].…”
Section: Discussionmentioning
confidence: 99%
“…Teledermatology can be cost‐effective or cost minimising when compared to traditional methods of delivering dermatological care . Both patients and providers report high satisfaction with teledermatology …”
Section: Evidence For Teledermatologymentioning
confidence: 99%